Waste electrical and electronic equipment (WEEE) handbook - Goodship, Vannessa; Stevels, Ab; Huisman, Jacob (Woodhead Publishing series in electronic and optical materials., 2019)
Waste Electrical and Electronic Equipment (WEEE) Handbook, Second Edition, is a one-stop reference on current electronic waste legislation initiatives, their impact, and the latest technological considerations for reducing electronic waste (e-waste) and increasing the efficiency of materials recovery. It also provides a wide-range of global and corporate examples and perspectives on the challenges that face specific regions and companies, along with the solutions they are implementing in managing e-waste, offering further insights on how discarded products can be treated. Sections introduce the reader to legislation and initiatives to manage WEEE and discuss technologies for the refurbishment, treatment and recycling of waste electronics. Further sections focus on electronic products that present particular challenges for recyclers, explore sustainable design of electronics and supply chains, discuss national and regional WEEE management schemes, and more.